Analysis of some problems about the sum of digits of a positive integers (Texas Journal of Multidisciplinary Studies, 2023)
This article presents analysis of some problems about the sum of digits of a positive integers. Problems about the sum of digits of a positive integer often occur in mathematical contests because of their difficulty and the lack of standard ways to tackle the problem. Therefore, in such cases, a analysis of common methods is useful.